Can end‐user feedback inform 'Responsibilisation' of India's policy landscape for agri‐digital transition?. Issue 2 (23rd April 2022) - Kumar, Anupam; Basu, Soutrik
Abstract: Agrarian transformations are imagined globally through digital agriculture. Most ambitious agrarian plans in India also identify the application of digital technologies to drive the next agro‐food revolution. However, the concerns around the 'soft impacts' of the agri‐digital transition, including socioethical concerns and farmers' perceptions, have received relatively little attention among innovators and policymakers. Thus, through a combination of qualitative content analysis and topic modelling, this article studies end‐user feedback on smart farming apps in India. Emerging themes from the feedback analysis inform an understanding of the attributes of responsibilisation in policies through which agri‐digitalisation is being planned and introduced. The main findings indicate that agri‐digital innovations need to be inclusive of nonhegemonic vernaculars, responsive to farmers' data privacy and ownership considerations and focus on producing simple, actionable insights for farmers instead of bombarding them with conflicting ideas. At the policy level, this article argues that the Indian policy landscape needs to be reformed substantially. This further suggests that India may need a new institutional architecture to manage the digital transition in agriculture.